CRC Handbook of Phase Equilibria and Thermodynamic Data of Polymer Solutions at Elevated Pressures - Wohlfarth, C. (CRC Press LLC, 2015)
"Thermodynamic data of polymer solutions are paramount for industrial and laboratory processes. These data also serve to understand the physical behavior of polymer solutions, study intermolecular interactions, and gain insights into the molecular nature of mixtures. Nearly a decade has passed since the release of a similar CRC Handbook and since then a large amount of new experimental data have been published, which is now compiled in this book."-- Provided by publisher
Keywords: Polymer solutions -- Thermal properties.; elektronické knihy; electronic books